Development of advanced pulmonary vascular disease in D-transposition of the great arteries after the neonatal arterial switch operation. - Rivenes, S M (1998)
We report the case of a neonate with D-transposition of the great arteries who, after undergoing an uneventful arterial switch operation at the age of 4 days, was found at the age of 42 months to have developed advanced pulmonary vascular disease. Because the arterial switch operation was performed when our patient was only 4 days old, this case challenges the hypothesis that postnatal hemodynamics alone dictate the development of advanced pulmonary vascular disease in infants and children with transposition of the great arteries.